Granulosa cell glycogen fuels the avascular corpus luteum - Jianning Liao; Qinghua Liu; Cong Liu; Guiqiong Liu; Xiang Li; Xiaodong Wang; Yaqin Wang; Ruiyan Liu; Hao Wu; Chaoli Wang; Hongru Shi; Yongheng Zhao; et al. (Proceedings of the National Academy of Sciences, 2026)
The corpus luteum (CL) arises from the luteinization of granulosa cells (GCs) and theca cells, marked by rapid progesterone elevation and angiogenesis. Intriguingly, angiogenesis lags behind progesterone elevation, creating an avascular phase during which luteal cells must fuel intensive steroidogenesis without perfusion. How the avascular CL meets this energetic demand remains a mystery. Here, we reveal a cellular adaptive mechanism—granulosa cell energy storage (GCES)—that resolves this enigma. We demonstrate that upon luteinization initiation, GCs enter a metabolically quiescent state yet enhance glucose uptake, converting the glucose into glycogen. Catabolism of this glycogen reserve supplies the energy required for the avascular CL, ensuring normal luteogenesis. Disruption of GCES induces luteal insufficiency, whereas timely glucose administration enhances GCES, improving luteal function and optimizing reproductive outcome in both mouse and ovine models. In human study, oral intake of glucose post-hCG significantly augments GCES and enhances progesterone production. These results advance our understanding of luteinization.